Cellular and metabolic impacts of repeated sub-acute exposures to biomass-burning extracts in vitro - Michal Pardo; Chunlin Li; Amani Jabali; Yinon Rudich (Ecotoxicology and Environmental Safety)
The increasing exposure to biomass-burning emissions underscores the need to understand their toxicological impacts on human health. In this study, we developed a laboratory model to evaluate the effects of single and repeated sub-acute exposures to water-soluble wood tar (WT) extracts, a product of biomass burning, on human lung, liver, and immune cells. Using representative cell lines for different tissues, we examined the cytotoxic effects under conditions mimicking sub-acute environmental exposure levels relevant to humans. Our findings indicate that repeated sub-acute exposures to water-soluble WT extracts significantly enhance the inflammatory response, evidenced by increased IL6, IL8, and TNFa cytokine levels, compared to a single exposure. Additionally, oxidative stress responses were more pronounced with increased lipid peroxidation and HMOX1, GCLC and CYP1A1 gene expression following repeated exposures. Metabolomics analyses of polar and lipid metabolites revealed changes related to energy production and consumption that emerge even after a single exposure at sub-acute levels and vary across different cell types representing the different tissues. Impaired cellular respiration, measured by oxygen consumption rate, corroborates the observed changes. These results provide important insights into the cellular mechanisms driving the response to biomass-burning exposure and highlight the potential health risks associated with sub-acute exposure to environmental pollutants.